2010
DOI: 10.1038/nsmb.1856
|View full text |Cite
|
Sign up to set email alerts
|

Corecognition of DNA and a methylated histone tail by the MSL3 chromodomain

Abstract: MSL3 resides in the MSL (male-specific-lethal) complex that upregulates transcription by spreading the H4K16 acetyl-mark. We discovered a DNA-dependent interaction of MSL3 chromodomain with the histone H4K20 monomethyl-mark. Structure of a ternary complex shows DNA minor groove accommodates the histone H4 tail, and monomethyllysine inserts in a four-residue aromatic cage in MSL3. Histone H4K16 acetyl-mark antagonizes MSL3 binding, suggesting MSL function is regulated by a combination of post-translational modi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
88
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 95 publications
(94 citation statements)
references
References 20 publications
4
88
2
Order By: Relevance
“…Possible Nucleic Acid Binding Surfaces on the MSL3 CBDIn addition to binding methylated histone tails, we observed that both hMSL3 and dMSL3 chromo-barrel domains bound strongly to nucleic acids when purified from bacterial cell lysates, and remained bound after glutathione-Sepharose affinity purification, an observation consistent with the recent determination of a hMSL3 CBD⅐DNA complex (36). We could only effectively remove contaminating nucleic acid using ionexchange chromatography (results not shown).…”
Section: Effect Of Msl3 Methyllysine Binding Pocket Mutations On Histsupporting
confidence: 68%
See 4 more Smart Citations
“…Possible Nucleic Acid Binding Surfaces on the MSL3 CBDIn addition to binding methylated histone tails, we observed that both hMSL3 and dMSL3 chromo-barrel domains bound strongly to nucleic acids when purified from bacterial cell lysates, and remained bound after glutathione-Sepharose affinity purification, an observation consistent with the recent determination of a hMSL3 CBD⅐DNA complex (36). We could only effectively remove contaminating nucleic acid using ionexchange chromatography (results not shown).…”
Section: Effect Of Msl3 Methyllysine Binding Pocket Mutations On Histsupporting
confidence: 68%
“…Comparison with a hMSL3 CBD:DNA H4K20 StructureRecently, a structure of the hMSL3 CBD bound to duplex DNA and H4K20Me 1 was published (36). In contrast to our results, that study concluded that methylated histone tail binding to hMSL3 or dMSL3 CBDs occurred only in the presence of double-stranded DNA and that histone tail binding was significant only for H4K20Me 1 and not other histone tail sequences or higher degrees of methylation.…”
Section: An Aromatic Cage Methyllysine Binding Pocket In Hmsl3-contrasting
confidence: 56%
See 3 more Smart Citations